English Spelling Game Design as Learning Media - Ikhwan Baidlowi Sumafta; Ardhitya Septian Gilang Ardhana; Moch Rangga Dizzy Pringgayuda; Muhammad Alfandi Nurcahyono (Jurnal Pendidikan Multimedia (Edsence), 2023)
In this digital era, the ability to use technology is a must that everyone must own, especially educators or teachers, so that they can provide teaching or material by utilizing technology. Understanding various foreign languages in the era of globalization in the 21st century is needed by all groups. So it is necessary to teach from an early age about learning and understanding foreign languages for children, especially learning English, an international language. Based on the background and previous research, it is necessary to have a learning media in the form of a game for learning English, especially in understanding spelling, so that students both at an early age and in elementary school students can be more motivated and enthusiastic in remembering the good and correct spelling of English.